Rapid thermal processing of chemical-solution-deposited yttrium-doped barium zirconate thin films - Xie, Hanlin (2017)
In this paper, dense and crack-free yttrium-doped barium zirconate (BZY) thin films were fabricated by chemical solution deposition (CSD) with rapid thermal processing (RTP) at low sintering temperature. BZY thin film without barium carbonate phase was obtainable after annealing at 700 °C for 1 h, which represents the lowest temperature reported in the literature. X-ray reflectivity study showed that the relative density of resultant BZY thin film was approximately 90%, indicating the effective densification of BZY at low temperature sintering by RTP. Microstructural analysis of BZY thin film showed that the film was dense, smooth and homogenous without cracks or interconnected pores. Thus, CSD method combined with RTP is promising for the fabrication of BZY electrolyte thin film due to the low processing temperature and high quality of the obtained film.